2021
DOI: 10.1007/s00392-021-01846-7
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, sedentary behavior and risk of coronary artery disease, myocardial infarction and ischemic stroke: a two-sample Mendelian randomization study

Abstract: Aims Observational evidence suggests that physical activity (PA) is inversely and sedentarism positively related with cardiovascular disease risk. We performed a two-sample Mendelian randomization (MR) analysis to examine whether genetically predicted PA and sedentary behavior are related to coronary artery disease, myocardial infarction, and ischemic stroke. Methods and results We used single nucleotide polymorphisms (SNPs) associated with self-reported m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 63 publications
(91 reference statements)
0
28
0
Order By: Relevance
“…Likewise, studies have shown a high heritability also for susceptibility to disease and longevity [78][79][80]. The lack of established causality between physical activity and CVD is further shown by mendelian randomization (MR) studies that have not been able to establish an association between genetically predicted accelerometermeasured physical activity and the risk of heart failure, coronary heart disease, myocardial infarction, and stroke [81,82]. Another MR study found that whereas genetic predisposition to a variety of metabolic risk factors and smoking were associated with lower odds of longevity, there was no such association for genetically predicted self-reported physical activity [83].…”
Section: Does Exercise Prevent Fractures In Older Adults?mentioning
confidence: 99%
“…Likewise, studies have shown a high heritability also for susceptibility to disease and longevity [78][79][80]. The lack of established causality between physical activity and CVD is further shown by mendelian randomization (MR) studies that have not been able to establish an association between genetically predicted accelerometermeasured physical activity and the risk of heart failure, coronary heart disease, myocardial infarction, and stroke [81,82]. Another MR study found that whereas genetic predisposition to a variety of metabolic risk factors and smoking were associated with lower odds of longevity, there was no such association for genetically predicted self-reported physical activity [83].…”
Section: Does Exercise Prevent Fractures In Older Adults?mentioning
confidence: 99%
“…Based on the sample size of the SLE GWAS meta-analysis, there was >80% power to detect associations of MVPA, VPA, SSOE, average acceleration, and sedentary behavior with the risk of SLE for an effect size (OR) of ∼ 0.834 ( Supplementary Table S3 ). All IVs for genetically predicted PA have been certified and applied in recent other MR studies ( Legge et al, 2020 ; Papadimitriou et al, 2020 ; Bahls et al, 2021 ; Julian et al, 2021 ). Additionally, all of them were irrelevant to smoking and alcohol drinking ( Supplementary Table S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…The differences registered between the samples of active and semi-active sports subjects were predominantly statistically significant for p < 0.05. The most important parameters regarding obesity and body composition that registered significant differences between the two male groups were in favor of the group of active athletes: triglyceride content of abnormal coefficient 0.844 (CI95% 0.590-1.099), abnormal lipid metabolism coefficient 0.798 (CI95% 1.091-0.504), obesity degree of body (ODB %) 10.290 (CI95% 6.610-13.970), BMI 2.326 (CI95% 1.527-3.126), body fat (kg) 2.042 (CI95% 0.918-3.166), muscle volume (kg) 2.565 (CI95% 1.100-4.031), Lean body weight (kg) 2.841 (CI95% 5.265-0.418). In the case of female samples, the group of active sportswomen registered the biggest differences compared to the group of students who were significantly active in the parameters: abnormal lipid metabolism coefficient 1.063 (CI95% 1.380-0.746), triglyceride content of abnormal coefficient 0.807 (CI95% 0.437-1.178), obesity degree of body (ODB%) 8.082 (CI95% 2.983-13.181), BMI 2.285 (CI95% 1.247-3.324), body fat (kg) 2.586 (CI95% 0.905-4.267), muscle volume (kg) 2.570 (CI95% 0.154-4.985), lean body weight (kg) 4.118 (CI95% 1.160-7.077).…”
Section: Introductionmentioning
confidence: 96%
“…Recent studies have highlighted the major risk of lack of exercise in correlation with the increased incidence of obesity in cardiovascular disease, various cancers, diabetes and COVID-19 [10][11][12][13][14]. Obesity is considered a chronic disease that is caused by a number of major risk factors for human health, including genetic factor, hormonal balance, body thermogenic capacity, sensitivity of the nerve nucleus that regulates appetite or need for food, habits and behaviors related to unbalanced diet and sedentary lifestyle [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%